EVALUASI MUTU PELAYANAN DAN HUBUNGAN ANTARA KEPUASAN KONSUMEN DAN PELAKSANAAN PELAYANAN KEFARMASIAN OLEH APOTEKER PENGELOLA APOTEK DI APOTEK-APOTEK KOTA KENDARI - Sunandar Ihsan; Putri Rezkya; Nur Illiyyin Akib (Halu Oleo University, 2014)
Pharmaceutical service quality relate to consumer’s satisfaction. Twenty five percent curage of patient can be found from good pharmaceutical sevice and 75% from drug usage. This study aimed to determine pharmaceutical service quality in community pharmacy of Kendari City and to determine correlation between consumer’s satisfaction and implementation of pharmaceutical service by pharmacist manager. This study is an observational analytic. Data collected from 519 respondents through questionnaires in June-August 2014 spread across ten community pharmacies City of Kendari with sampling method used simple random sampling, and accidental sampling for pharmacist manager. Correlation test used to determine correlation between cons umer satisfaction and implementation of pharmaceutical care by pharmacist manager in pharmacy. The result showed that the percentage rate is 76.70% for consumer satisfaction with moderate category. Fixed percentage of any document procedures and dispensing time is 60% with moderate category. Pharmacist manager percentage that manages quality guarantee is 40% with less category. Statistic correlation test showed that there is no cerrelation between consumer satisfaction and implementation of pharmaceutical care by pharmacist manager in pharmacy with p value 0,268 (> 0,05). Keywords: quality service, pharmaceutical service, consumer satisfaction